(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In modern cardiology practice, determining cardiac troponin levels serves as the "gold standard" for verifying acute myocardial infarction. This article presents a comprehensive analysis of the evolution of laboratory methods for detecting troponins I and T, highlighting the significant increase in the analytical sensitivity of modern test systems. The author examines the problem of interpreting subclinical biomarker concentrations, which arises with the introduction of highly sensitive methods (high-sensitivity troponin, hs-Tn).